PENGARUH MOTIVASI, STRESS KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. BPR REJEKI INSANI SUKOHARJO - Rohman, Ervan Nur; Hendarti, Yanita (Universitas Of Surakarta, 2022)
This study aims to determine the effect of motivation, work stress, and work discipline on the performance of employees of PT. BPR Rejeki Insani Sukoharjo (Case Study at PT. BPR Rejeki Insani Sukoharjo Branch) either partially or simultaneously. This research is a quantitative research. The data used is primary data collected using a questionnaire. This study used 53 respondents as the research sample. The analytical technique used in this research is multiple linear regression analysis test, F test, t test, and coefficient of determination test. The results showed that motivation, work stress, and work discipline partially had a significant effect on employee performance. These three variables have a significant effect on employee performance simultaneously.